Mechanisms of glucocorticoid pro-inflammatory effects on CCL20: crosstalk and synergy - Nhundu, Tawanda (Department of Molecular and Cell Biology, 2019)
Glucocorticoids (GCs) are steroid hormones widely prescribed to treat inflammatory disorders and are regarded as anti-inflammatory molecules. GCs classically induce the expression of antiinflammatory genes, while repressing pro-inflammatory genes via its endogenous cell receptor; the glucocorticoid receptor (GR). Emerging evidence, however, suggests that the mechanisms of GR action are more complex than previously assumed, with many reports of pro-inflammatory actions of GCs via the GR. While chronic exposure to GCs has been noted as anti-inflammatory, reports suggest that acute exposure can increase peripheral immune responses. Specifically, the GCs have been shown to positively regulate the innate immune response, which may be important in preventing the local, affected area from being immunocompromised. Furthermore, the GR can crosstalk with cell signalling pathways involved in pro-inflammatory responses, such as the TNFα pathway, to reciprocally modulate the expression of pro-inflammatory genes. The mechanisms behind the GR’s pro-inflammatory actions and crosstalk with inflammatory inducers are not well understood. GC’s pro-inflammatory actions are attributed to GC insensitivity in asthma patients. The insensitivity is attributed to long-term GC usage, and the increase in Th17 neutrophilic airway infiltration. A proposed hypothesis for the increase in neutrophils in the airways was that it was due to an increase in expression of chemokines by epithelial cells due to GC exposure. The pro-inflammatory, chemoattractant cytokine C-C motif chemokine ligand 20 (CCL20) has been previously shown to be induced by GCs and pro-inflammatory inducers in human bronchial cells, with positive modulation of their responses occurring with co-stimulation. The present study investigated whether the GC dexamethasone (dex) and the pro-inflammatory inducer TNFα could induce CCL20 expression in a variety of human epithelial cell lines, and a simian fibroblast cell line. Using Real-Time Quantitative Reverse Transcription PCR (qRT-PCR), it was confirmed that dex can induce CCL20 mRNA expression, and modulate the TNFα-induced expression in some, but not all cell lines. Moreover, in the HeLa cell line, there was an apparent synergistic response between dex and TNFα, and modulation of the CCL20 response was observed between dex and the pro-inflammatory inducers phorbol 12-myristate 13-acetate (PMA), interferon γ (IFNγ) and lipopolysaccharide (LPS). The GR was shown to be required for the GC induction and modulation of CCL20 mRNA expression. Using promoter-reporter assays, the results showed that the NFκB binding site was necessary for the activation by the pro-inflammatory inducers, but not dex, while the STAT binding region was necessary for the IFNγ activation. Interestingly, lack of the STAT binding site on the promoter-reporter construct caused IFNγ to have repressive effects on CCL20 activation. Stimulation of cells by the pro-inflammatory inducers in the presence or absence of dex had no effect on the total levels of the p65 subunit of NFκB, while dex did appear to cause GR turnover as expected. The results show that dex, via the GR, is able to crosstalk with different pro-inflammatory inducers to induce and potentiate CCL20 mRNA expression and promoter activation. The mechanisms of CCL20 induction and crosstalk with the GR may be different for each proinflammatory inducer, however. Regulation of CCL20 expression is complex, with many transcription factors converging on the promoter region to modulate its expression. This thesis shows that the NFκB binding site is important for the overall induction level of the promoter, however it is not necessary for the dex induced activation. The potentiation of the dex response by pro-inflammatory inducers may be due to the GR interacting with the AP-1 and C/EBP transcription factors, which have been shown to positively interact to increase gene expression. The potentiation of the dex response does not require the activation of NFκB, as IFNγ does not activate the transcription factor, yet can potentiate the dex response.